ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KREATIVITAS AKUNTAN - Aviv, Rachman; Muid, Dul (Diponegoro Journal of Accounting, 2014)
This study aims to examine the influence of internal factors for the creativity accountans. Accounting is considered as the science is far from creativity. This causes an accountant is prevented from being creative possibilities. Accountants will be closed opportunities and the chance to be creative. This study examined the influence of ethics to the creativity accountant by Bryant, et al (2011) and Nurcahyo (2012). Ethics is measured using the dimensions of idealism and relativism. In addition, this study also examines the effect of job tenure, gender and intellectual of the creativity accountant.The population of this study is the auditor who works in the firm in the city of Semarang. The sample was an auditor who works in the firm in the city of Semarang with sampling techniques through sampling covinience. Data were collected through questionnaires and analyzed using multiple regressions.The results showed that the job tenure and gender had no effect on creativity accountant. In addition, intellectual and relativism significantly positive effect on creativity accountant. Idealism significantly negative effect on creativity accountant.